Web development & design foundations with XHTML / Terry Felke-Morris - Morris, Terry (Terry A.) (Pearson/Addison Wesley, 2007)
Web Development and Design Foundations with XHTML, 3/E includes everything begineers need to develop highly effective Web sites. Besides providing comprehensive coverage of XHTML, this book introduces the Web design and development process and offers successful strategies for promoting Web sites, including accessibility and standards.